Visual Loss without Headache in Children with Pseudotumor Cerebri and Growth Hormone Treatment - Besch, Dorothea; Makowski, Christine; Steinborn, Marc-Matthias; Bonfig, Walter; Sadowski, Bettina (Neuropediatrics, 2013)
We report on two prepubescent girls with visual loss due to idiopathic intracranial hypertension (IIH), or pseudotumor cerebri, both treated with recombinant human growth hormone for growth failure. The interval from starting hormone therapy to diagnosis of IIH was 3 and 18 months, respectively. Both girls did not complain of headache and nausea. They were neither obese nor did they suffer from renal insufficiency. In both patients, we observed bilateral optic disc edema with visual loss and elevated cerebrospinal fluid (CSF) pressures. Other causes of IIH were excluded with neuroimaging and CSF examination. Cessation of drug administration is often sufficient for symptom resolution in cases of hormone therapy–associated IIH. However, visual field defects in one girl remained unchanged during follow-up of 8 months. In children with IIH, the spectrum of neurologic and visual manifestations might be variable and unspecific. Diagnosis and management of IIH can be difficult in the absence of headache. Blurred or double vision due to cranial nerve palsy might be the only symptom rather than complaints about reduced visual acuity. Therefore, regular clinical monitoring of visual function and fundus appearance is essential for early diagnosis, efficient management, and improvement of visual outcome in children receiving recombinant human growth hormone.
Keywords: pediatric pseudotumor cerebri; pediatric idiopathic intracranial hypertension; growth hormone; papilledema; visual loss